INFLUENCE OF PSYCHO-EMOTIONAL COMPONENT AND THE PHYSIOLOGY OF ORGAN OF VISION ON RELIABLE DETERMINATION OF THE COLOR CHARACTERISTICS OF TOOTH IN RESTORATIVE DENTISTRY - Shilenko, D.R.; Pisarenko, E.A.; Удальцова, К.О.; Dubina, V.A.; Clepach, N.N.; Khavalkina, L.M. (World of Medicine and Biology, 2012)
The analysis of the available literature data about influence of emotional status of the doctor and the patient to a fair determination of color in aesthetic dentistry. It was shown the influence of physiology of the organ of vision on the process of color-identification.